LONG-TERM RISKS OF EARLY INITIATION OF BREASTFEEDING TO MOTHERS AND INFANTS IN ASIA: A SYSTEMATIC REVIEW - Ajay Varmaa Jeyaseelan; Raisa Nurwany; Syifa Alkaf (Universitas Andalas, 2024)
Objective: This systematic review aims to determine the long-term risks of early initiation of breastfeeding in mothers and babies in Asia. Method: The method used in writing this literature review is systematization using keywords, namely